The Contribution of Epistemic Curiosity and its Relevance to Science Process Skills on Biology Prospective Teacher - Hunaepi Hunaepi; Muhammad Ikhsan; Hadi Suwono; Sulisetijono Sulisetijono (Postgraduate, University of Mataram, 2021)
The purpose of this study was to determine the contribution of epistemic curiosity (EC) to the science process skills (SPS) of prospective biology teachers. Ex post facto research design with research subjects 32 students of the third-semester biology education study program at the Mandalika University of Education. Samples were taken using the purposive sampling method. The instruments used were the State Curiosity Scale (SCS) to collect epistemic curiosity data, Student Worksheets, and the Science Process Skills rubric to collect SPS. The results showed that the magnitude of the correlation value or R relationship was 0.600. From the output, the coefficient of determination (R Square) was 0.359, this shows that EC is correlated with SPS. Meanwhile, in terms of the results of simple regression analysis, it was found that the variable X (EC) obtained the value of t-count = 4.103 > 1.697 t-table and sig. = 0.000 < 5%. This means that the EC variable contributes significantly to the SPS variable. The results obtained have not been able to describe the contribution of EC to each SPS indicator, so further research needs to analyze the contribution of EC to each SPS indicator